A Review of the Smart Grid Communication Technologies in Contactless Charging with Vehicle to Grid Integration Technology - Abdulgader Alsharif; Tan Chee Wei; Razman Ayop; Kwan Yiew Lau; Abba Lawan Bukar (Journal of Integrated and Advanced Engineering (JIAE), 2021)
Power needs to be transferred from the source to the load (electric vehicle). Transmitting electricity through the air gap for charging using electromagnetic waves as one of the smart grid technologies called Wireless Power Transfer (WPT), or Inductive Power Transfer. This paper presents the fulfilment of future gird that addresses the issues of Greenhouse Gas emission, and transportation and industries emissions known as the smart grid with a complex system. The complexity of the smart grid communication system is the motivation to be an open area of research issue. The main contribution of this paper is to close the gap between this research and other researches by delivering a comprehensive review and update the recent state-of-the-art of smart grid communication technologies with the integration of vehicle-to-grid (V2G) technology using the contactless charging method. Smart grid communication technologies with their pros and cons, topologies of wireless communication, challenges of the V2G, WPT challenges, and standards are discussed. Therefore, this study is expected to be a significant guide to engineers and researchers studying in the field of smart grid communication technologies and contactless charging for electric vehicles.